Free Fall Motion Learning Design with Tracker Software to Improve Graphic Literacy - Nurfaizal; Khairil Anwar; Zulkarnain (Indonesian Journal Of Educational Research and Review, 2023)
Physics learning is process skill-based learning. One of the science process skills that students must master is graphic literacy. The material on free fall motion is a lesson that requires students to have graphic literacy skills, but the facts in the field show that not a few of the students have difficulty reading and managing information based on graphs. This study aims to analyze the improvement students' graph literacy, which was conducted at Senior High School. The research subjects were students, the research sample amounted to 21 students of class X MIA. Using a quasi-experimental method with a quantitative approach, one group pre-post test design. The research instruments used pretest and posttest questions, modules, and LKS. Data analysis using JASP software to get t-test results and Ngain. The results showed that there was a significant difference in students' graphic literacy skills before and after using the video tracker as indicated by the results of the paired samples t-test at a sig value. (P) 0,001 < 0,05. Each indicator of students' graphic literacy has increased even though not all are at high criteria. Students mastery of science literacy can easily solve problems about regular straight-line motion.